2022
DOI: 10.1101/2022.02.08.479273
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Resistance bioassays and allele characterisation inform analysis ofSpodoptera frugiperda(Lepidoptera: Noctuidae) introduction pathways in Asia and Australia

Abstract: The fall armyworm Spodoptera frugiperda is present in over 70 countries in Africa, Asia, and Oceania. Its rapid dispersal since 2016 since first reported in western Africa, and associated devastation to agricultural productivity, highlight the challenges posed by this pest. Currently, its management largely relies on insecticide sprays and transgenic Bacillus thuringiensis toxins, therefore understanding their responses to these agents and characteristics of any resistance genes enables adaptive strategies. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 81 publications
(234 reference statements)
0
14
0
Order By: Relevance
“…In China, Lv et al (2021) reported diamide resistance alleles in individuals from Guangxi and Guizhou Provinces. While this study failed to source Indonesian and Cambodian populations (due to the difficulty of sharing and sending biological material from Indonesia and Cambodia to Australia), significant differences in resistance to indoxacarb was nevertheless detected between WA (Kununurra) and Qld (Strathmore) populations (Tay et al 2021a, Tay et al 2022c, and could be due to the different source populations for the WA and the Qld populations. On-going studies to monitor for potential arrivals of novel resistance alleles and those already reported in Indonesia and China to Australia will therefore be needed to inform and impact future FAW management strategies.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…In China, Lv et al (2021) reported diamide resistance alleles in individuals from Guangxi and Guizhou Provinces. While this study failed to source Indonesian and Cambodian populations (due to the difficulty of sharing and sending biological material from Indonesia and Cambodia to Australia), significant differences in resistance to indoxacarb was nevertheless detected between WA (Kununurra) and Qld (Strathmore) populations (Tay et al 2021a, Tay et al 2022c, and could be due to the different source populations for the WA and the Qld populations. On-going studies to monitor for potential arrivals of novel resistance alleles and those already reported in Indonesia and China to Australia will therefore be needed to inform and impact future FAW management strategies.…”
Section: Discussionmentioning
confidence: 94%
“…While multiple introductions especially in the Asian continent (e.g., China, Vietnam, Malaysia; Vu 2008, Nguyen and Vu 2009, Tay and Gordon 2019, Gui et al 2020, Tay et al 2021b, Jiang et al 2022, Tay et al 2022d; this study) have played an important role leading to the perception of rapid spread, introductions from elsewhere have also contributed to the African establishment and expansion. Further to genomics evidence, resistance allele characterisation and bioassay experiments have also identified invasive populations with non-overlapping unique insecticide resistance profiles in China (e.g., Lv et al 2021), Indonesia (Boaventura et al 2020), Australia (Tay et al 2021a, Tay et al 2022c), India (Deshmukh et al 2020), and Africa (Eriksson 2019, Worku and Ebabuye 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations